PENGARUH KETIDAKPUASAN KONSUMEN, IKLAN, PERSEPSI HARGA, DAN PERILAKU MENCARI VARIASI TERHADAP PERPINDAHAN MEREK (Studi PadaKonsumen Pasta Gigi Ciptadent di Kota Semarang) - Mya Maulida Hurriyah, 15.05.51.0261; Maskur, Ali (Students' Journal of Economic and Management, 2019)
The purpose of this study was to determine the effect of consumer dissatisfaction, advertising, price perceptions, and variation seeking behavior on the transfer of the Ciptadent brand in the city of Semarang. The population in this study were consumers who had used Ciptadent toothpaste products in the city of Semarang. The sampling technique used purposive sampling. The sample criteria in this study are consumers of Ciptadent toothpaste and have moved brands, consumers aged over 17 years, and domiciled in the city of Semarang. The analytical tool used is multiple linear regression. The results of the study can be concluded that: consumer dissatisfaction has a positive and significant effect on brand displacement, advertising has a negative and not significant effect on brand displacement, price perception has a positive and significant effect on brand displacement, and variation seeking behavior has a positive and significant effect on brand shift.